Microalgae Biotechnology - Posten, Clemens; Feng Chen, Steven; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Antenna Mutants, Domestication, by Roberto Bassi Heterotrophic Cultivation, by William McCaffrey Chlorella for industrial applications: Advances and prospective, by Feng Chen Carotinoide, by Carola Griehl Engineering the algal chloroplast for synthesis of therapeutic proteins, by Saul Purton Design Concepts and recent developments of photobioreactors, by Clemens Posten Efficiency of flat plate reactors, by Mario Tredici Measuring modelling and control, by Olivier Bernard Microalgae in Life Support Systems, by Klaus Slenzka Heterotrophic oil production, by Makato Watanabe.
Antenna Mutants, Domestication -- Heterotrophic Cultivation -- Chlorella for industrial applications: Advances and prospective -- Carotinoide -- Engineering the algal chloroplast for synthesis of therapeutic proteins -- Design Concepts and recent developments of photobioreactors -- Efficiency of flat plate reactors -- Measuring modelling and control- Microalgae in Life Support Systems -- Heterotrophic oil production.
Keywords: Biotechnology; Microbiology; Chemistry, Technical; Biotechnology; Microbiology; Industrial Chemistry